ANALYZING FUZZY MATRICES AND CONNECTIVITY IN SPECTRAL FUZZY GRAPH THEORY - K., Senbaga Priya; R., Buvaneswari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this paper, an analysis is conducted on several fuzzy matrices associated with a fuzzy graph, including the adjacency matrix A(G) and the Laplacian matrix L(G). The eigenvalues of the adjacency matrix (λi) of a fuzzy graph and their properties are stated and discussed. Fuzzy vertex connectivity (κ), along with algebraic connectivity (ϑn−1), adjacency, and Laplacian eigenvalues, are studied under conditions κ ≤ q to make contributions to spectral fuzzy graph theory, enhancing the connectivity in network structures due to the occurrence of linguistic and inexact variables. Additionally, the relation- ship between κ and ϑn−1 shows the strength of connectivity among the vertices.